2015
DOI: 10.1111/jgs.13609
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Visuospatial Ability and Vestibular Function in the Baltimore Longitudinal Study of Aging

Abstract: OBJECTIVES To investigate the relationship between vestibular loss associated with aging and age-related decline in visuospatial function. DESIGN Cross-sectional analysis within a prospective cohort study. SETTING Baltimore Longitudinal Study of Aging (BLSA). PARTICIPANTS Community-dwelling BLSA participants with a mean age of 72 (range 26–91) (N = 183). MEASUREMENTS Vestibular function was measured using vestibular-evoked myogenic potentials. Visuospatial cognitive tests included Card Rotations, Purdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
76
1
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(89 citation statements)
references
References 48 publications
3
76
1
9
Order By: Relevance
“…However, impairments in visual spatial abilities, measured by other assessment tools, are related to poorer mathematical abilities and achievement, which have been associated with higher risk of unemployment and lower lifetime earnings (Dumontheil and Klingberg, 2012; Li and Geary, 2013; Sella et al, 2016; Slot et al, 2016; Wei et al, 2012). Deficits in visual spatial abilities can also affect quality of life and activities of daily living, including navigational ability, vestibular function, autobiographical memory, and social interactions in terms of recognizing social signals and interpersonal space (Bigelow et al, 2015; Janssen et al, 2015; Rodriguez et al, 2015). However, Penta-BDE congeners BDE-47, −99, and −100 at 5 and 8 years were associated with reduced Virtual Morris Water Maze completion time by 4–5 seconds.…”
Section: Discussionmentioning
confidence: 99%
“…However, impairments in visual spatial abilities, measured by other assessment tools, are related to poorer mathematical abilities and achievement, which have been associated with higher risk of unemployment and lower lifetime earnings (Dumontheil and Klingberg, 2012; Li and Geary, 2013; Sella et al, 2016; Slot et al, 2016; Wei et al, 2012). Deficits in visual spatial abilities can also affect quality of life and activities of daily living, including navigational ability, vestibular function, autobiographical memory, and social interactions in terms of recognizing social signals and interpersonal space (Bigelow et al, 2015; Janssen et al, 2015; Rodriguez et al, 2015). However, Penta-BDE congeners BDE-47, −99, and −100 at 5 and 8 years were associated with reduced Virtual Morris Water Maze completion time by 4–5 seconds.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Video recordings of consenting patients before and after intervention help to further document these obvious alterations in ways that complement standardized neuropsychology testing. [5][6][7][8][9][10][11][12][13][14][15][16][17][18] Other investigators have also explored the relationship between vestibular dysfunction and cognitive dysfunction; [19][20][21][22][23][24][25][26][27][28] however, Gizzi and coworkers used the Neurobehavioral Symptom Inventory, and the Beck Depression Inventory and reported no causal connection between vestibular disorders and cognitive dysfunction. 28 They studied 200 patients with "dizziness""-half with a history of brain trauma and half without.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, those tests are included in the core battery as useful cognitive indicators to assess motor–cognitive interaction . SDST measures several cognitive mechanisms, including visual information processing such as visual attention and visuoperceptual and visuospatial ability . Sánchez‐Cubillo et al .…”
Section: Discussionmentioning
confidence: 99%
“…1 SDST measures several cognitive mechanisms, including visual information processing such as visual attention and visuoperceptual and visuospatial ability. 26,27 Sánchez-Cubillo et al summarized 24 studies that examined the cognitive processes underlying TMT performance, and identified that visual search, perceptual/motor speed, speed of processing, and working memory were the most frequently cited constructs thought to contribute to TMT performance. 28 Thus, SDST and TMT are characterized as using cognitive domains, including: (i) ability to capture visually the numbers and their places (visuoperceptual ability); (ii) ability to focus on important parts of the information and ignore unnecessary parts (visual attention); (iii) ability to memorize the location of a number seen once (visuospatial memory); and (iv) ability to manage and process that information (execution function).…”
Section: Constructive Validity Of the S-tmtmentioning
confidence: 99%